Peranan Jaksa Pengacara Negara dalam Menyelesaikan Kasus Mewakili Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan di Denpasar - Gusti Ayu Ajeng Prabaningtyas; Nyoman Putu Budiartha; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2021)
The prosecutor as the recipient of the power of attorney in a special power of attorney, which in this case represents employment BPJS, handles legal issues related to entrepreneurs who have not registered themselves and staff as members of the Manpower Dependent Program. The purposes of this study are to reveal the role of state attorneys in resolving cases representing the Social Security Administering Body (BPJS) for employment in Denpasar and the efforts of state attorneys to resolve cases representing BPJS for employment in Denpasar. This type of research is sociological with an empirical juridical approach. Data collection techniques were carried out by literature study, observation, interviews related to this research. Sources of data used in the form of secondary and primary data which are then analyzed systematically. The results of the study indicate that the role of the State Attorney's Attorney in resolving cases representing BPJS Ketenagakerjaan as a legal counsel with a Special Power of Attorney to resolve the company has not recorded itself and its staff in the Manpower Dependent Program. While the efforts of State Lawyers in resolving cases representing BPJS Ketenagakerjaan, with a Special Power of Attorney from BPJS Ketenagakerjaan, State Attorneys act in terms of providing non-litigation legal assistance by mediating business entities and individuals who do not register as members of the Employment Social Security Agency or have not complied with the payment of fees